2013
DOI: 10.5114/fn.2013.37707
|View full text |Cite
|
Sign up to set email alerts
|

Original article Disturbed regulation of the isolated middle cerebral artery in acute hyponatremia

Abstract: A b s t r a c t Hyponatremia is a common disorder of water-electrolyte balance characterized by the decrease of plasma sodium ions concentration below 135 mM. Although water-electrolyte balance is regulated by a kidney, symptoms of hyponatremia are related to the disturbances of intracranial homeostasis and are attributed to brain swelling. Despite the importance of blood vessels function for the homeostasis of the brain, little is known about the influence of hyponatremia on cerebrovascular regulation. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Despite the importance of blood vessels function for the homeostasis of the brain, little is known about the influence of hyponatremia on cerebrovascular regulation 7. One previous study demonstrated that the dilatation of the cerebral vessel in response to acetylcholine, which is endothelium and nitric oxide dependent, was severely impaired in hyponatremia 8. Cerebral hypoxia due to vasoconstriction probably makes impairment of brain adaptation due to dysfunction of Na+ − K+ − ATPase, which is primary importance for the extrusion of ions from the glial cell 9.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of blood vessels function for the homeostasis of the brain, little is known about the influence of hyponatremia on cerebrovascular regulation 7. One previous study demonstrated that the dilatation of the cerebral vessel in response to acetylcholine, which is endothelium and nitric oxide dependent, was severely impaired in hyponatremia 8. Cerebral hypoxia due to vasoconstriction probably makes impairment of brain adaptation due to dysfunction of Na+ − K+ − ATPase, which is primary importance for the extrusion of ions from the glial cell 9.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies indicate that acute hyponatremia, which was induced in vitro without the presence of vasopressin, did not affect autoregulation, but blunted the response of the MCA to ACh, NO donor, and acidosis [ 4 , 5 ]. Acute hyponatremia also decreased the sensitivity of the BK Ca channels in vascular smooth muscle cells to agonists [ 4 ], which would explain the impaired response of the MCA to the abovementioned vasodilators.…”
Section: Discussionmentioning
confidence: 99%
“…RAS activation can also lead to plaque rupture in atherosclerotic lesions, along with with cardiac and brain damage [19,20]. Third, a study has shown that hyponatremia impairs NOdependent vasodilatation in cerebral artery [21]. Dysregulation of perfusion in cerebral vessels is possibly related to occurrence of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%